The Roles of Zakat Towards Maqasid Al-Shariah and Sustainable Development Goals (SDGs): A Case Study of Zakat Institutions in East Malaysia - Ag Omar, Pg Mohd Faezul Fikri; Hajimin, Mohd Nur Hidayat Hasbollah (Center of Strategic Studies (PUSKAS) BAZNAS, 2023)
Purification of wealth, eradication of poverty, and socio-economic development are among zakat’s frequently claimed ultimate purposes. A sound zakat management system is goal-oriented and works to achieve those goals. Zakat collection and distribution activities must materialise zakat objectives by applying objectives-driven techniques. This study examines how zakat management, collection, and distribution are consistent with Maqasid Al-Shariah and the Sustainable Development Goals (SDGs). This qualitative study in nature analyses secondary data from East Malaysian zakat institutions. The study’s findings indicate that both zakat institutions in East Malaysia, namely the Bahagian Zakat dan Fitrah of the Sabah Islamic Religious Council (MUIS) and the Tabung Baitulmal Sarawak of the Sarawak Islamic Council (MIS), are operating following the Maqasid Al-Shariah objectives and several Sustainable Development Goals (SDGs) agenda. Both zakat institutions should strive for continuous improvement.